Spatiotemporal analysis of 3D kinematic asymmetry in professional cycling during an incremental test to exhaustion. Issue 19 (2nd October 2018) - Pouliquen, Camille; Nicolas, Guillaume; Bideau, Benoit; Garo, Gérard; Megret, Armand; Delamarche, Paul; Bideau, Nicolas
ABSTRACT: This study investigated the influence of an incremental exercise on bilateral asymmetry through the spatio-temporal evolution of 3D joint angular displacement, using the Normalized Symmetry Index ( ) and cross-correlation methods. Twelve professional cyclists performed an incremental test to exhaustion, during which motion capture was used. Results revealed a decrease in range of motion between the first and last stages for twelve of the eighteen joint rotations, with the highest impact observed for right hip flexion/extension (61.8 ± 4.7° to 58.8 ± 4.1°, p < 0.05, ES = 0.68). For both stages, significant bilateral differences greater than 10° were observed for hip and knee flexion/extension (p < 0.05, ES>0.90) and ankle and hip internal/external rotation (p < 0.05, ES>0.25). Cross-correlation displayed the lowest pattern similarities for hip abduction/adduction and the highest similarities for knee flexion/extension, ankle plantarflexion/dorsiflexion and hip internal/external rotation. The cross-correlation method showed that the right leg was mostly ahead of time with respect to the left leg, a trend that was accentuated with power output increase. Instantaneous fluctuated up to 18% throughout the pedalling cycle, with different behaviour between the power and recovery phases. This study demonstrated the workload effects on side-to-side joint angular pattern similarity.